Kandungan Mineral Hijauan Rumput Rawa Sebagai Pakan Kerbau Pampangan di Sumatera Selatan - Muhakka, Muhakka; Suwignyo, R.A.; Budianta, D.; Yakup, Yakup (Seminar Nasional Lahan Suboptimal, 2018)
Muhakka et al, 2019.Â Mineral Content of Forage Swamp Grass as Pampangan Buffalo FeedÂ in South Sumatera. pp. 82-92.This study aims to analyze the mineral content of swamp forage vegetation as feed for pampangan buffalo. This research was carried out in Rambutan Village and Pulau Layang Village. This research is a descriptive study to describe the mineral content of swamp forage vegetation as feed for pampangan buffalo. Parameters observed were content of Calcium (Ca), Phosphorus (P), Sodium (Na), Iron (Fe), Aluminum (Al), Cobalt (Co) and Selenium (Se). Mineral content of swamp forage vegetation varies. The content of Ca with a range of 0.041 - 1.170%, with the lowest Ca of kumpai tembaga (Hymenachne acutigluma) and the highest of Are Bolong (Polygonum barbatum L). P content ranged from 0.020 - 0.181%, the lowest content of kerak maling grass and the highest kumpai minyak (Hymenachne amplexicaulis). Na content ranges from 0.005 - 0.362%, the lowest content of kumpai tembaga (Hymenachne acutigluma) and the highest kumpai minyak (Hymenachne amplexicaulis). Fe content ranges from 0.003 - 0.005%, the lowest content of kumpai tembaga grass (Hymenachne acutigluma) and the highest kerak maling grass. Al content ranges from 1,815 - 182,29 ppm, with the lowest content of kumpai tembaga grass. The best mineral content of forage swamp vegetation is kumpai tembaga, are bolong, kerak maling and telepuk gajah.